Informality and the Moral Perception of Paying Fair Payroll Taxes – A Perspective on Institutional Quality Influence - Nuta, Alina Cristina; Tanasa, Florentin (The Journal of Accounting and Management, 2024)
In this article, we aim to realize an assessment of the economic literature on fiscal morality (the attitude of individuals towards taxes and especially towards tax payment) and its relationship to tax compliance (the final behavior of the individual in the context of the social contract with the state) in the wider set of informality and free-rider problem. Our research aims to identify the elements that lead to the shaping of informality, starting from the fiscal morality approach in a world in which poverty and inequality put additional pressure on individuals’ decisions about taxes.